The Influence of Pre-entry Attributes Academic and Social Integration on Persistence and Academic Success Among First- Generation African American Lgbtq+ Students at Hbcus in the Southeastern United States - Brown, Curtis E.; Okojie, Felix A. (Advances in Social Sciences Research Journal, 2026)
This qualitative study examined persistence and achievement of first-generation, Black LGBTQ+ students at HBCUs in the southeastern U.S. While HBCUs promote cultural affirmation, the intersectional experiences of these students remain underexplored. Guided by Tinto’s Student Departure Theory, the study explored how pre-entry traits, academic, and social integration influence persistence through semi-structured interviews at two HBCUs. Thematic analysis found family, spirituality, and being first-generation shaped motivations and challenges. Academic integration relied on faculty relationships and institutional support, especially identity-affirming classrooms. Social factors like peer relationships, campus culture, and safe spaces impacted belonging. Many students made sacrifices to stay committed, often without support. Results highlight HBCUs' cultural affirmation but gaps in supporting LGBTQ+ and first-generation students. Recommendations include expanding affirming spaces, better faculty training on inclusion, and improved advising, mentorship, and counseling. Future research should examine long-term outcomes and how institutions can better serve diverse students.